Screening Characters 2019
DOI: 10.4324/9780429422508-13
|View full text |Cite
|
Sign up to set email alerts
|

absorbed character engagement

Abstract: …there's a part of you that…you've grown accustomed to not sharing with other people.It's a very private, intimate personal aspect of yourself, and then all of a sudden you see it reflected in something other than yourself. A sense of acknowledgement, that you're being acknowledged. That's why I call it positive. It's an affirmation that the ideas you have, the emotions you have, aren't yours alone; they're things that are found in others that you can share. That's what I got from this film." -Participant 18 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Our participants remarked that they were more interested in and identified more with fictional characters based on their position and roles in the story [the protagonist (n: 6), someone the protagonist knows (n: 2) or the character who is responsible for the unfolding of events (n: 1)], which is consistent with the literature. Bálint and Tan (2019) interviewed a group of 25 people between the ages of 21-72 with different ethnic backgrounds and found that they were more interested in the protagonists' inner worlds than other characters. Çevik and Müldür (2019) found that almost all students (25 out of 28) wanted to be one of the characters around the protagonist (except the protagonist's mother) or one of the characters in the book.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants remarked that they were more interested in and identified more with fictional characters based on their position and roles in the story [the protagonist (n: 6), someone the protagonist knows (n: 2) or the character who is responsible for the unfolding of events (n: 1)], which is consistent with the literature. Bálint and Tan (2019) interviewed a group of 25 people between the ages of 21-72 with different ethnic backgrounds and found that they were more interested in the protagonists' inner worlds than other characters. Çevik and Müldür (2019) found that almost all students (25 out of 28) wanted to be one of the characters around the protagonist (except the protagonist's mother) or one of the characters in the book.…”
Section: Discussionmentioning
confidence: 99%
“…We are also interested in how some aspects of the reading experience may affect the generation of SPSs. Bálint and Tan (2019) observed that readers spontaneously and frequently mentioned similarities and desired similarities with fictional characters when they described their highly absorbed narrative experiences. Thus, we believe that some dimensions of state Story World Absorption (Kuijpers et al, 2014) may relate to the activation of storyworld possible selves.…”
Section: Present Studymentioning
confidence: 99%